Hubungan Kecanduan Game Online dengan Kualitas Tidur dan Motivasi Belajar - Widiarti, Tri; Istiani, Hari Ghanesia; Rokhmiati, Eka (Journal of Nursing Education and Practice, 2024)
Background: Online game addiction is a very strong feeling towards something that one wants. The impacts that influence online game addiction are disrupted sleep quality and decreased motivation to study. Objective: To determine the relationship between addiction and sleep quality and learning motivation among students at MTS Nurul Islam Bogor City in 2022. Method: This type of research is quantitative with a Cross-Sectional approach, the sample used in this research was 60 people taken using the Total Sampling technique. The data collection technique uses a questionnaire instrument. The analysis used the Chi-Square test. Results: The results obtained on the relationship between online game addiction and sleep quality resulted in a P-value of 0.05 and OR 0.58. A significant relationship between online game addiction and learning motivation was obtained with a P-value of 0.02 and an OR of 8.5. Conclusion: There is a relationship between online game addiction and sleep quality and study motivation at MTS Nurul Islam Bogor City in 2022.